Architecture for Publication and Universal Access to Smart Transducers - Lima Ribeiro, Alexandre Alves de; Rodrigues da Silva, Alexandre Cesar [UNESP]; IEEE (Ieee, 2012)
This paper proposes a simple and powerful architecture for publication and universal access to smart transducers, through existing and established open standards. Smart transducers are put to work on standards and styles already included in the Web, exploring resources in Cloud Computing and simplifying access to data.